How Tax Capital Group May Influence on Tax Aggressiveness: Polish Perspective - Alicja BRODZKA; Krzysztof BIERNACKI; Damian STASZAK (Communications of International Proceedings, 2020)
In the paper we look at the issue of tax aggressiveness from the perspective of enterprises that, in accordance with the provisions of Polish tax law, may establish a tax capital group (TCG). Focusing on companies from banking sector we study, to what extent such an entity can reduce its tax liability and how profitable a creation of TCG vehicle can be. In order to answer the question we use individual tax data provided by companies with annual turnover above EUR 50 million and all Polish tax capital groups. For years 2012–2019, we calculate the annual effective tax rates achieved by the largest taxpayers from the banking sector. In the next step, we compare the tax rates achieved by single entities with those reported within banking tax capital groups. In order to deepen the research, we additionally calculate the average annual effective tax rates of both groups: single companies and banking TCGs. The results of the study show that the vehicle of tax capital group is rarely used by Polish companies operating in the banking sector, nor leads to the reduction of their tax liabilities.
Keywords: Tax Aggressiveness; Tax Group; Group Taxation; Tax Risk; Tax Avoidance.